(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article maps out the activities of those religious organizations which take on the missionary character, special attention being given to the Protestant ones. Under different headings are explained the reasons for the growth of such missionary movements and the employed techniques. Is tackled in the article the problem of proselytism, which as a result of multi-dimensional religious expansion and the intense activity of missionary movements has come to be seen as a threat to the unity and spiritual unity in such a country as Kirgizstan – a country which in terms of religious tolerance and interfaith friendship of its peoples has been considering itself a role model for the neighbouring countries (and to which some experts have referred as not less than the “Switzerland of Asia” and “Island of democracy “ in Central Asia). In this country, proselytism possesses potential to cause serious religious conflicts. The key words: missionary organizations, enculturation, proselytism, freedom of conscience and religion.